Modulation of functional properties of bi-functional S-Adenosylmethionine decarboxylase / Ornithine decarboxylase of Plasmodium falciparum by structural motifs in parasite-specific inserts - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.